2018
DOI: 10.1590/1678-7757-2017-0318
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a food enriched with probiotics on Streptococcus mutans and Lactobacillus spp. salivary counts in preschool children: a cluster randomized trial

Abstract: Probiotics have provided benefits to general health, but they are still insufficient to dental health.Objective:This study aimed to evaluate milk supplemented with probiotic bacteria and standard milk, measured by levels of Streptococcus mutans (S. mutans) and Lactobacillus spp., in 3-4-year-old children after 9 months of intervention.Material and Methods:The study was a triple-blind, placebo-controlled, randomized trial. The sample was composed of 363 preschoolers attending five child development centers in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 26 publications
3
51
0
3
Order By: Relevance
“…When the confounding factors, including age, sex, and the number of surfaces with noncavitated and cavitated active caries at baseline, were controlled, both daily and triweekly probiotic consumption prevented dental caries by reducing caries increment and significantly increasing the regressive surfaces compared to the placebo group at the 6-and 12-month follow-up periods. Our results are consistent with previous findings in young children that showed decreased numbers of carious surfaces or of affected children with caries after longterm intakes of milk containing various Lactobacillus species [Näse et al, 2001;Stecksen-Blicks et al, 2009;Rodriguez et al, 2016;Villavicencio et al, 2018]. At the outset, consumption of milk containing L. rhamnosus GG was shown to significantly reduce caries risk levels that were determined by caries status and MS counts [Näse et al, 2001].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…When the confounding factors, including age, sex, and the number of surfaces with noncavitated and cavitated active caries at baseline, were controlled, both daily and triweekly probiotic consumption prevented dental caries by reducing caries increment and significantly increasing the regressive surfaces compared to the placebo group at the 6-and 12-month follow-up periods. Our results are consistent with previous findings in young children that showed decreased numbers of carious surfaces or of affected children with caries after longterm intakes of milk containing various Lactobacillus species [Näse et al, 2001;Stecksen-Blicks et al, 2009;Rodriguez et al, 2016;Villavicencio et al, 2018]. At the outset, consumption of milk containing L. rhamnosus GG was shown to significantly reduce caries risk levels that were determined by caries status and MS counts [Näse et al, 2001].…”
Section: Discussionsupporting
confidence: 92%
“…In addition, consumption of milk containing L. rhamnosus LB21 demonstrated 75% prevents fraction and new caries prevention so that 21% of the participants remained caries-free [Stecksen-Blicks et al, 2009], and children who consumed milk containing L. rhamnosus SP1 exhibited significantly less caries incidence than those who consumed the placebo [Rodriguez et al, 2016]. However, the most recent study instead reported that consumption of milk containing a combination of L. rhamnosus and Bifidobacteruim longum, which are commercially available as infant formula powder, did not reduce the risk of initial caries [Villavicencio et al, 2018]. This inefficacy may be attributed to the lack of bacterial strain or caries specificity [McFarland et al, 2018].…”
Section: Discussionmentioning
confidence: 99%
“…(20) Villavicencio et al showed that administration of probiotics significantly reduced lactobacilli in preschool children. (21) In this study, 56.9% of participants never prescribed a casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) for their patients.…”
Section: Discussionmentioning
confidence: 86%
“…Additionally, analyzing saliva will not necessarily render data on S. mutans biofilm count. In the first study mentioned previously, 376 there was a reduction in Lactobacilli spp. and an increase in the buffering capacity of saliva, but no evaluation of caries rate was reported.…”
Section: Dental Caries and Cariologymentioning
confidence: 78%
“…In a triple-blind, placebo-controlled, randomized trial, Villavicencio et al 376 evaluated the effect of milk supplemented with probiotic bacteria, compared with standard milk, on levels of S. mutans and Lactobacillus spp., in 3-to 4-year-old children after 9 months of intervention. Participants included 363 preschoolers attending 5 childdevelopment centers in Cali, Colombia.…”
Section: Dental Caries and Cariologymentioning
confidence: 99%